2021
DOI: 10.1002/alr.22832
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae in adults at 12 months after mild‐to‐moderate coronavirus disease 2019 (COVID‐19)

Abstract: We conducted a prospective study on mild-to-moderate symptomatic patients consecutively assessed between March 1 and March 31, 2020, who tested positive for SARS-CoV-2 RNA by polymerase chain reaction (PCR) on nasopharyngeal and throat swabs performed according to World Health Organization recommendation. An interdisciplinary task force of medical doctors and nurses was created in our region in response to the COVID-19 pandemic in order to monitor all isolated patients with PCRconfirmed SARS-CoV-2 infection. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 10 publications
11
87
3
Order By: Relevance
“…Both presenting patient characteristics and clinical management have evolved since. The generalizability of our results may be limited by the potential patient population selection bias, lack of standardized validated questionnaires for reporting the prevalence of COVID-19 symptoms at the international level and the self-reporting of symptoms based on a remote interview (19) as well as the study's single-center, not-blinded, and not-randomized design.…”
Section: Strenghts and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both presenting patient characteristics and clinical management have evolved since. The generalizability of our results may be limited by the potential patient population selection bias, lack of standardized validated questionnaires for reporting the prevalence of COVID-19 symptoms at the international level and the self-reporting of symptoms based on a remote interview (19) as well as the study's single-center, not-blinded, and not-randomized design.…”
Section: Strenghts and Limitationsmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) is a severe acute respiratory infection caused by the emergent coronavirus, SARS-CoV-2. Though most infected individuals are asymptomatic, SARS-CoV-2 infection may cause symptoms ranging from mild to severe acute respiratory distress, with a substantial fraction of patients requiring hospitalization (estimated to be around 10%) and many patients experiencing prolonged symptoms and complications for weeks or months after the initial period of acute illness [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 3-7 months follow-ups of COVID-19 patients, ageusia, dysgeusia and hypogeusia persisted in 1.6-7.3% of Chinese and Japanese patients [40,43,52], but in 5.0-42% of French, Italian, American, Norwegian, Israeli, German, and British patients [41,42,[44][45][46][47][48][49][50][51][53][54][55]. For longer follow-up time (to 12 months), gustatory (and olfactory) dysfunction was observed in 25.8% of Israeli patients [57], 12.7% of Italian patients [58] and 22.0% of Italian patients [59]. Persistent gustatory dysfunction is likely to be less prevalent in Asian patients compared with patients in other countries, suggesting that ethnicity may be a risk factor to prolong gustatory dysfunction in COVID-19 survivors.…”
Section: Ethnicitymentioning
confidence: 99%
“…Thus, a dysregulated host immune response was identified that causes a life-threatening cytokine storm and subsequent immune paralysis, leading to multiple organ failure and death. And even though mild-tomoderate COVID-19 does not seem to be associated with a fulminant immune activation, more and more data point to long lasting infection related sequelae including persisting nausea, fatigue and loss of smell and taste in up to 30% of patients who recovered from COVID-19 (10)(11)(12). Hence, even non-severe COVID-19 may pose a considerable hazard for global health and economy.…”
Section: Introductionmentioning
confidence: 99%